DIAPHRAGMATIC HERNIA - Alam, Malik Mahmood (Journal of Ayub Medical College Abbottabad, 2016)
This three hours old girl was transferred to Valley Hospital from another Private Hospital. She was born full term by C-section due to poor progress in 2nd stag. She had low Apgars at birth and needed bagging and then intubation. She was also given intravenous antibiotics and steroids. She was immediately shifted to the Valley Hospital by intermittent positive pressure ventilation through endotracheal tube. On arrival she was blue and had saturations of 25% with heart rate of 130/min. Her tube was dislodged during transfer and therefore she was briefly bagged and intubated with size 3.5 tube. Her saturations went up to 80% but no air entry was heard on left side. Immediate x-ray was taken and it showed diaphragmatic hernia on left side and extending up to right side as well. Congenital Diaphragmatic hernia is seen in 1 of every 2000-4000 live births. 84% of these occur on left side 13% on right side and 2% are bilateral.1 Most of the congenital hernias are detected on antenatal ultrasound scans2 or soon after birth due to difficulty in breathing. Mortality is due to pulmonary hypoplasia. Fetal MRI may be performed to detect diaphragmatic hernia.3,4 Postnatally Chest x-ray will show the intestines in the chest with lung hypoplasia. Delivery of the babies should be in the tertiary unit with facilities for neonatal surgeries and ECMO.5